USING TWO-TIER DIAGNOSTIC TEST INSTRUMENT TO ANALYZE GENDER DIFFERENCES IN MISCONCEPTION IN LINEAR MOMENTUM - Daniel Nti; Eric Appiah-Twumasi; Frederick Ameyaw; Collins Agyemang (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2022)
Misconceptions that occur can vary between male and female students. The purpose of this study was to analyze gender difference in misconceptions in linear momentum. The diagnostic- descriptive research method was used in this study. A total of 70 (35 males and 35 females) first-year Senior High School students in the La-Nkwantanan Municipality were used for this study. Identification of misconceptions was conducted using the Two-tier multiple-choice diagnostic test instrument that was equipped with the Certainty of the Response Index method. The study showed both males' level of understanding and misconception (56.88%; 42.88%) and females (28.51%; 50.24%), respectively. An independent sample t-test revealed that male’s students understanding of concept was statistically more than females and misconception was found not be statistically significantly different. The two-tier multiple-choice instrument could be used as an alternative instrument to identify misconceptions among students. The results of this study are expected to be a reference for Physics educators to identify and resolve students' misconceptions.